2003
DOI: 10.1037/0096-3445.132.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of the Monty Hall problem: Discovering psychological mechanisms for solving a tenacious brain teaser.

Abstract: The Monty Hall problem (or three-door problem) is a famous example of a "cognitive illusion," often used to demonstrate people's resistance and deficiency in dealing with uncertainty. The authors formulated the problem using manipulations in 4 cognitive aspects, namely, natural frequencies, mental models, perspective change, and the less-is-more effect. These manipulations combined led to a significant increase in the proportion of correct answers given by novice participants, largely because of the synergy of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(135 citation statements)
references
References 25 publications
5
130
0
Order By: Relevance
“…Fractions are hard to understand whereas collections seem to be easy (Brase, Cosmides, & Tooby, 1998), as illustrated by the almost universal use of fi ngers as a representational system (Butterworth, 1999(Butterworth, , 2001, and brain imaging studies suggest that key number areas are closely connected to the fi nger circuit (Dehaene, Spelke, Pinel, Stanescu, & Tviskin, 1999). Krauss and Wang (2003) studied the notorious Monty Hall problem, which most adults fail at, and showed that correct answers can be facilitated by changing the single-event question ("should I switch or not switch doors") into a frequency question ("in how many cases will switching win? "), and Krauss and Atmaca (2004) showed similar facilitation for children and adolescents aged 11 to 19.…”
Section: Resultsmentioning
confidence: 99%
“…Fractions are hard to understand whereas collections seem to be easy (Brase, Cosmides, & Tooby, 1998), as illustrated by the almost universal use of fi ngers as a representational system (Butterworth, 1999(Butterworth, , 2001, and brain imaging studies suggest that key number areas are closely connected to the fi nger circuit (Dehaene, Spelke, Pinel, Stanescu, & Tviskin, 1999). Krauss and Wang (2003) studied the notorious Monty Hall problem, which most adults fail at, and showed that correct answers can be facilitated by changing the single-event question ("should I switch or not switch doors") into a frequency question ("in how many cases will switching win? "), and Krauss and Atmaca (2004) showed similar facilitation for children and adolescents aged 11 to 19.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it is often possible for an incorrect answer to be justified. Probability calculations are frequently counterintuitive, and groups may adopt socially plausible but inappropriate strategies This phenomenon is illustrated by the history of the Monty Hall problem, where incorrect solutions are frequently more persuasive than correct solutions (Krauss & T, 2003).…”
Section: Allowing Experts To Interact Is Possibly a Good Ideamentioning
confidence: 99%
“…Then you are asked if you want to keep your first choice or switch to the third choice, before seeing what is under both. The correct decision is to switch, because you double your odds of winning (Selvin, 1975), but few people appreciate why that has to be true (Krauss & Wang, 2003). More often, people will stick with their first choice because they are afraid to find out they were right but then switched (Burns & Wieth, 2004;Gilovich, Medvec, & Chen, 1995), or they will switch (or stay) because they say it no longer matters, and the odds are 50:50 for winning.…”
Section: The Monty Hall Problem and Misrepresenting Probabilitymentioning
confidence: 99%